2010
DOI: 10.1007/s10384-010-0826-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel snapshot imaging of photoreceptor bleaching in macaque and human retinas

Abstract: The topography of bleached photoreceptors obtained with a commercial fundus camera from one monkey and three healthy human subjects showed that this technique has potential as a new clinical method for examining photoreceptor function in both normal and diseased retinas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Kazato et al[ 42 ] showed that the retinal reflectance at the fovea was higher than that at the parafovea which is consistent with our results. They suggested that the retinal reflectance depended on the cone density as we have.…”
Section: Discussionsupporting
confidence: 93%
“…Kazato et al[ 42 ] showed that the retinal reflectance at the fovea was higher than that at the parafovea which is consistent with our results. They suggested that the retinal reflectance depended on the cone density as we have.…”
Section: Discussionsupporting
confidence: 93%
“…Reflectometry may suffer from media opacities and macular pathology that will complicate image acquisition and that may invalidate the assumptions in the underlying mathematical model. Only a few reflectometry studies have been carried out with commercial instrumentation in Europe and Japan (Kazato et al, 2010; van de Kraats et al, 2008), and it is concerning that results do not correlate well when tested head-to-head against AFI or HFP in the same patients (Dennison et al, 2013). Resonance Raman imaging can also be implemented in a chemically specific imaging mode, but required light levels approach ANSI limits, so only a few normal volunteers have been imaged (Sharifzadeh et al, 2008).…”
Section: Carotenoids and Eye Disease And Function Throughout The Lmentioning
confidence: 99%
“…The spatial distribution of the reflectance changes was determined later by examining images obtained by either a fundus camera or a scanning laser ophthalmoscope (SLO), that is, imaging fundus reflectometry. [23][24][25][26][27][28][29][30][31][32][33] With these techniques, the distribution of photoreceptors was mapped objectively and non-invasively as bleach-derived light reflectance changes in normal and diseased eyes. However, the responses of the different types of photoreceptors, especially rods and S-cones, could not be segregated accurately because the response time courses were not monitored accurately.…”
mentioning
confidence: 99%